Metal-free synthesis of calixsalen-type cavitands for the recognition of fluoride ion. Issue 3 (1st February 2018) - Desai, Arpita; Rana, Dharti
ABSTRACT: Novel calixsalen-type cavitands have been synthesized using metal-free synthesis from simple and inexpensive materials, such as ethylenediamine and 5, 5′-methylene-bis-salicylaldehyde derivatives. The cavitand 1 containing salen functionality recognizes fluoride ion. Fluoride ions switch on fluorescence on binding with the cavitand 1. Substitution on bis-salicylaldehyde part of calixsalen-type cavitand shows change in recognition behavior. On the attachment of electron withdrawing substituent, such as nitro group, the cavitand lost its fluorescence properties but proved to be a better colorimetric probe showing marked color change from pale yellow to red on addition of tetrabutyl ammonium salt of fluoride ion to the solution of cavitand. The nitro substituted cavitand is highly sensitive and selective for fluoride anion and hence is a promising candidate for development of colorimetric chemosensor. The binding of the cavitands with fluoride ion is investigated using 1 H NMR-titration experiments. GRAPHICAL ABSTRACT: